2017
DOI: 10.1002/tea.21425
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of science‐rich resources to public science interest

Abstract: This preliminary study examined the effect that five major sources of public science education-schools, science centers, broadcast media, print media, and the Internet-had on adults' science interest values and cognitive predispositions. Over 3,000 adults were sampled in three U.S. metropolitan areas: Los Angeles, California, Phoenix, Arizona, and Philadelphia, Pennsylvania. To minimize potential sampling bias, the results were weighted by current U.S. Census data to be comparable to demographics from each of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 49 publications
0
24
1
Order By: Relevance
“…Third, our data collection relied on verbal self‐reports by the teachers, which were obtained during the postintervention interviews. While self‐reports have been used by a number of studies (cf., Chan, ; Diamond, Maerten‐Rivera, Rohrer, & Lee, ; Falk, Pattison, Meier, Bibas, & Livingston, ) they are not always seen as the most reliable sources of data (cf., Tourangeau, Rips, & Rasinski, ). For the purpose of our setting, however, we consider them a suitable method, as self‐reports allow for the immediate collection of data.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our data collection relied on verbal self‐reports by the teachers, which were obtained during the postintervention interviews. While self‐reports have been used by a number of studies (cf., Chan, ; Diamond, Maerten‐Rivera, Rohrer, & Lee, ; Falk, Pattison, Meier, Bibas, & Livingston, ) they are not always seen as the most reliable sources of data (cf., Tourangeau, Rips, & Rasinski, ). For the purpose of our setting, however, we consider them a suitable method, as self‐reports allow for the immediate collection of data.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of a learning experience that promotes participation and science teaching in an active learning environment has positive effects on all children regardless of their literacy and social origin. Indeed, this approach has been found to create a rich learning environment that is accessible to all the students in the classroom (Fantuzzo et al, 2011;Sarama et al, 2012). Furthermore, studies have shown that there is a correlation between positive experiences in science as a child and a strong interest in and a positive perception of science as an adult (Falk et al, 2017).…”
Section: Oh-kids: a Stem Outreach Modelmentioning
confidence: 99%
“…Furthermore, studies have shown that there is a correlation between positive experiences in science as a child and a strong interest in and a positive perception of science as an adult (Falk et al, 2017). The model is akin to a workshop and includes two types of activities.…”
Section: Oh-kids: a Stem Outreach Modelmentioning
confidence: 99%